Preparation of bulk modified graphene and diaphragm method

Bulk-modified graphene is prepared by reacting potassium permanganate with natural graphite and laser shaping. Combined with in-situ polymerization and spinning processes, the problems of low yield and uniformity in graphene preparation are solved, the performance of the diaphragm is improved, and it is suitable for high temperature and high pressure environments.

CN120698449APending Publication Date: 2025-09-26PEKING UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511211149.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-28
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

Existing graphene preparation methods have low yields, many defects and complex processes, making it difficult to achieve uniform control of the graphene bulk structure, resulting in low ion conductivity and poor thermal stability of the diaphragm material in lithium-ion batteries.

Method used

Potassium permanganate is mixed with natural graphite and reacted in concentrated sulfuric acid to form a graphite oxide precursor. The precursor is then treated with an ultrasonic cell crusher and combined with laser pulse shaping and photochemical effects to prepare bulk-modified graphene. The graphene is then in situ polymerized with substances such as 2-(4-aminophenyl)-5-aminobenzimidazole to form a modified graphene-reinforced heterocyclic aramid resin. Finally, a modified diaphragm is prepared by spinning and casting.

Benefits of technology

The high crystallinity and uniform modification of graphene are achieved, the mechanical properties and thermal stability of the diaphragm are improved, the toughness of the aramid fiber and the ion conductivity of the diaphragm are enhanced, and it is suitable for high temperature and high pressure environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120698449A_ABST
    Figure CN120698449A_ABST
Patent Text Reader

Abstract

On the basis of synthesizing graphene oxide by a conventional Hummer method, graphene with a complete lamellar structure is prepared by adopting a 2-5 DEG C temperature control mode, and graphene nanoplatelets are shaped and partially reduced through laser pulses to improve the crystallinity of the graphene nanoplatelets, so that the complete lamellar structure and an aramid fiber raw material are found; substances such as phenylenediammonium, diamine containing a heterocyclic structure, 2-(4-aminophenyl)-5-aminobenzimidazole and the like can form a very stable acting force, so that the modification of the graphene is realized. The problem that impurities are introduced due to the fact that a surfactant needs to be added in the process of compositing the materials is indirectly solved, the raw material of aramid fiber is not used as a surfactant originally, and due to the fact that the adding amount of graphene is very small (0.01%-0.1%), the graphene is used for modifying phenylenediamine, diamine containing a heterocyclic structure, 2-(4-aminophenyl)-5-aminobenzimidazole and other substances.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanomaterial preparation and energy storage, and in particular to a method for preparing bulk-modified graphene and a diaphragm. Background Art

[0002] Graphene is an allotrope of carbon. It is a high-strength and high-toughness two-dimensional material. It is synthesized through molecular design and customization to form flaky graphene with a certain crystalline structure and a microscopic morphology. In the process of making diaphragms from flaky graphene, it is necessary to disperse it in aramid resin and guide the orientation of the aramid resin molecular chains during the spinning process to greatly improve the toughness of the modified aramid fiber.

[0003] When graphene is dispersed within an aramid resin membrane, it guides the orientation of the aramid resin molecular chains during the spinning process, significantly improving the toughness of the modified aramid fiber. Furthermore, graphene has strong mechanical properties and can be used as a strength reinforcement for aramid, significantly increasing its tensile strength and reducing its elongation at break.

[0004] However, traditional graphene preparation methods, such as mechanical exfoliation and redox methods, suffer from low yields, numerous defects, and complex processes. Furthermore, the modification process often focuses on surface modification, making it difficult to achieve uniform control of the graphene's bulk structure. Existing separator materials in lithium-ion batteries also suffer from low ionic conductivity and poor thermal stability. Summary of the Invention

[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.

[0006] To achieve the above-mentioned object, the present invention proposes a method for preparing bulk-modified graphene and a diaphragm, comprising the following steps: S1. Raw material pretreatment: natural graphite and potassium permanganate are mixed in a mass ratio of 1:1, and added to concentrated sulfuric acid to form a graphite oxide precursor. Then, a modifier is added, and the temperature is raised to 50°C for reaction for 2 hours to complete bulk doping; S2. Graphene exfoliation and reduction: The graphite oxide precursor was rapidly frozen in liquid nitrogen and then treated with an ultrasonic cell crusher for 1 hour to achieve interlayer exfoliation. Ascorbic acid was then added and reacted at 90°C for 4 hours to repair lattice defects through a reduction reaction. Finally, the temperature was controlled at 2-5°C to achieve the preparation of complete lamellar graphene and obtain bulk modified graphene. S3. Laser pulses are used to reshape graphene microsheets: The laser's photothermal and photochemical effects are used to reshape the graphene sheets, and the crystallinity of the graphene sheets is reduced and improved.

[0007] In addition, the bulk-modified graphene preparation and diaphragm method proposed in the present application may also have the following additional technical features: Specifically, in S1, natural graphite and potassium permanganate are mixed in a mass ratio of 1:1, added into concentrated sulfuric acid, and stirred at 0° C. for 30 minutes to obtain a graphite oxide precursor.

[0008] Specifically, the photothermal effect in S3 mainly uses the high energy density of the laser to ablate the lamellar graphene. By utilizing this, graphene microsheets can be precisely cut to produce specific shapes, patterns or holes; the laser can selectively remove the graphene layer to achieve thickness control of the lamellar graphene.

[0009] Specifically, the photochemical effect in S3 utilizes the high temperature induced by the laser to promote the reaction of graphene with the surrounding environment, leading to oxidation and introducing oxygen-containing functional groups into the graphene lattice, which can change the hydrophilicity and chemical activity of graphene; secondly, laser pulses are an effective means of reducing graphene oxide, and the photochemical effect of the laser can quickly remove oxygen-containing functional groups and restore part of the sp2 carbon network structure.

[0010] A method for bulk-modified graphene membrane comprises the following steps: Q1. Preparation of 2-(4-aminophenyl)-5-aminobenzimidazole-modified graphene: Using an in-situ polymerization method, the flake graphene prepared in S3 is dispersed in a liquid monomer, and 2-(4-aminophenyl)-5-aminobenzene is added to the liquid monomer. 2-(4-aminophenyl)-5-aminobenzene is then in situ polymerized in the presence of graphene. The monomer molecules can penetrate between the graphene sheets, and after polymerization, the polymer chains grow directly on the graphene surface or between the sheets. Thus, 2-(4-aminophenyl)-5-aminobenzimidazole-modified graphene can be obtained. Q2. Preparation of graphene-modified reinforced heterocyclic aramid resin: Using a polymerization reaction method, terephthaloyl chloride / acid is added to the 2-(4-aminophenyl)-5-aminobenzimidazole-modified graphene prepared in Q1; a near-infrared laser is then used to irradiate the monomer mixture of 2-(4-aminophenyl)-5-aminobenzimidazole-modified graphene and terephthaloyl chloride / acid; and the graphene absorbs light energy and converts it into heat energy, thereby locally heating and inducing thermal polymerization, thereby obtaining a graphene-modified reinforced heterocyclic aramid resin. Q3. Preparation of graphene-modified reinforced heterocyclic aramid fiber: The graphene-modified reinforced heterocyclic aramid resin in Q2 and an organic solvent such as N,N-dimethylacetamide and calcium chloride are mixed and dissolved. After cooling, diamine monomers such as 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine are added. After dissolution, the mixture is cooled again. Then, a diacyl chloride such as terephthaloyl chloride is added. The mixture is stirred at a certain temperature at high speed for polycondensation to obtain a polymer. In this process, the polymerization reaction is carried out in the solution, and the generated polymer is dissolved in the solvent to form a homogeneous system. The heterocyclic aramid fiber is then obtained through a spinning process. Q4. Preparation of graphene-modified reinforced heterocyclic aramid membrane: heterocyclic aramid resin and solvent are prepared into resin solution; graphene / pore-forming agent is added to the resin solution, and the resin solution is dispersed by ultrasound to ensure the casting stability of the resin solution; secondly, it is deaerated and filtered, and cast into a film, while using coagulation bath phase separation and solvent exchange to reduce the drying stress of the graphene-modified reinforced heterocyclic aramid membrane; finally, hot pressing is performed to increase the density of the graphene-modified reinforced heterocyclic aramid membrane.

[0011] Specifically, the liquid monomer in Q1 is selected from monomers with good solubility and low viscosity, such as MMA, ε-caprolactam, epoxy resin and other liquid monomers.

[0012] Specifically, the spinning process in Q3 introduces a high-intensity magnetic field into the pipes and spinnerets at both ends of the spinning plate, 1 cm to 50 cm away from the nozzle, and through a spinning speed of 1200 m / min, heterocyclic aramid fibers with mechanical properties of 4.8 GPa can be spun.

[0013] Specifically, in Q4, the resin solution needs to be stirred at 60° C. for 6 hours before adding graphene / pore-forming agent to the resin solution; secondly, the degassing filtration will be adopted to filter the solution through a 100 μm filter mesh, and the thickness of the film will be controlled by a slot coater.

[0014] Specifically, the coagulation bath phase separation and solvent exchange in Q4 are as follows: placing the membrane in a mixture of water and ethanol for 3-5 minutes to cause non-solvent-induced phase separation, wherein ethanol and n-hexane undergo gradient replacement to reduce drying stress; finally, the membrane is subjected to a hot pressing treatment at 180°C / 5MPa for 10 minutes to increase the density of the membrane.

[0015] Compared with the prior art, the present invention has the following advantages: 1. Based on the conventional Hummer method for synthesizing graphene oxide, a temperature control method of 2~5℃ is used to achieve the preparation of graphene with complete lamellar structure, and the graphene microsheets are shaped and partially reduced by laser pulses to improve their crystallinity.

[0016] 2. The complete lamellar structure and aramid raw materials, such as phenylenediamines, heterocyclic diamines, and 2-(4-aminophenyl)-5-aminobenzimidazole, form a very stable interaction, thereby modifying graphene. This indirectly solves the problem of impurities introduced by the addition of surfactants during the composite material process. Aramid raw materials are not originally used as surfactants. Due to the small amount of graphene added (0.01% to 0.1%), it is the graphene that modifies phenylenediamines, heterocyclic diamines, and 2-(4-aminophenyl)-5-aminobenzimidazole.

[0017] 3. Graphene modified by phenylenediaminium, diamine containing heterocyclic structure, 2-(4-aminophenyl)-5-aminobenzimidazole and other substances can also be regarded as graphene-modified phenylenediaminium, diamine containing heterocyclic structure, 2-(4-aminophenyl)-5-aminobenzimidazole and other substances, which undergo amidation reaction with another component of aramid synthesis, thereby preparing graphene-modified aramid resin or aramid-modified graphene by bulk polymerization.

[0018] Additional aspects and advantages of the present invention will be set forth in part in the description which follows and, in part, will be obvious from the description which follows, or may be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which: Figure 1 A schematic diagram of the overall structure of the graphene preparation method provided by the present invention; Figure 2 This is a schematic diagram of the overall structure of the graphene diaphragm method provided by the present invention. DETAILED DESCRIPTION

[0020] The embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention and are not to be construed as limiting the present invention. On the contrary, the embodiments of the present invention include all variations, modifications, and equivalents that fall within the spirit and scope of the appended claims.

[0021] See also Figure 1-2 The present invention provides a method for preparing bulk-modified graphene and a diaphragm, comprising the following steps: S1. Raw material pretreatment: natural graphite and potassium permanganate are mixed in a mass ratio of 1:1, and added to concentrated sulfuric acid to form a graphite oxide precursor. Then, a modifier is added, and the temperature is raised to 50°C for reaction for 2 hours to complete bulk doping; S2. Graphene exfoliation and reduction: The graphite oxide precursor was rapidly frozen in liquid nitrogen and then treated with an ultrasonic cell crusher for 1 hour to achieve interlayer exfoliation. Ascorbic acid was then added and reacted at 90°C for 4 hours to repair lattice defects through a reduction reaction. Finally, the temperature was controlled at 2-5°C to achieve the preparation of complete lamellar graphene and obtain bulk modified graphene. S3. Laser pulses are used to reshape graphene microsheets: The laser's photothermal and photochemical effects are used to reshape the graphene sheets, and the crystallinity of the graphene sheets is reduced and improved.

[0022] In one embodiment of the present invention, Figure 1 As shown in Figure 1, in S1, natural graphite and potassium permanganate are mixed in a mass ratio of 1:1, added to concentrated sulfuric acid, and stirred at 0°C for 30 minutes to obtain a graphite oxide precursor; then, aminosilane or borate modifier is added and reacted at 50°C for 2 hours to complete the doping of the bulk.

[0023] Furthermore, the photothermal effect in S3 mainly uses the high energy density of the laser to ablate the lamellar graphene. By utilizing this, graphene microsheets can be precisely cut to create specific shapes, patterns or holes; the laser can selectively remove the graphene layer to achieve thickness control of the lamellar graphene; the photothermal effect of the laser mainly uses local heating to ablate the lamellar graphene, wherein local heating utilizes the laser energy absorbed by the graphene, especially in the visible and near-infrared bands, and is rapidly converted into heat, thereby causing the local temperature to rise sharply, so this can be used to precisely cut graphene microsheets, wherein the lower energy laser pulses can gently heat the graphene, promote the rearrangement of carbon atoms, reduce lattice defects such as vacancies and Stone-Wales defects, and repair damage introduced by irradiation or chemical treatment, thereby improving electrical properties and increasing carrier mobility; if the graphene is on a substrate, the laser thermal effect may also affect the substrate, thereby indirectly affecting the adhesion, stress or electronic properties of the graphene.

[0024] Furthermore, the photochemical effect in S3 utilizes the laser-induced high temperature to promote the reaction of graphene with the surrounding environment, leading to oxidation and introducing oxygen-containing functional groups into the graphene lattice, which can change the hydrophilicity and chemical activity of graphene; secondly, laser pulses are an effective means of reducing graphene oxide. The photochemical effect of the laser can quickly remove oxygen-containing functional groups and restore part of the sp2 carbon network structure; therefore, laser pulses can be used to reshape graphene microsheets and partially reduce them to improve their crystallinity.

[0025] As another aspect of the present invention, a method for bulk-modified graphene membrane is also provided, comprising the following steps: Q1. Preparation of 2-(4-aminophenyl)-5-aminobenzimidazole-modified graphene: Using an in-situ polymerization method, the flake graphene prepared in S3 is dispersed in a liquid monomer, and 2-(4-aminophenyl)-5-aminobenzene is added to the liquid monomer. 2-(4-aminophenyl)-5-aminobenzene is then in situ polymerized in the presence of graphene. The monomer molecules can penetrate between the graphene sheets, and after polymerization, the polymer chains grow directly on the graphene surface or between the sheets. Thus, 2-(4-aminophenyl)-5-aminobenzimidazole-modified graphene can be obtained. Q2. Preparation of graphene-modified reinforced heterocyclic aramid resin: Using a polymerization reaction method, terephthaloyl chloride / acid is added to the 2-(4-aminophenyl)-5-aminobenzimidazole-modified graphene prepared in Q1; a near-infrared laser is then used to irradiate the monomer mixture of 2-(4-aminophenyl)-5-aminobenzimidazole-modified graphene and terephthaloyl chloride / acid; and the graphene absorbs light energy and converts it into heat energy, thereby locally heating and inducing thermal polymerization, thereby obtaining a graphene-modified reinforced heterocyclic aramid resin. Q3. Preparation of graphene-modified reinforced heterocyclic aramid fiber: The graphene-modified reinforced heterocyclic aramid resin in Q2 and an organic solvent such as N,N-dimethylacetamide and calcium chloride are mixed and dissolved. After cooling, diamine monomers such as 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine are added. After dissolution, the mixture is cooled again. Then, a diacyl chloride such as terephthaloyl chloride is added. The mixture is stirred at a certain temperature at high speed for polycondensation to obtain a polymer. In this process, the polymerization reaction is carried out in the solution, and the generated polymer is dissolved in the solvent to form a homogeneous system. The heterocyclic aramid fiber is then obtained through a spinning process. Q4. Preparation of graphene-modified reinforced heterocyclic aramid membrane: heterocyclic aramid resin and solvent are prepared into resin solution; graphene / pore-forming agent is added to the resin solution, and the resin solution is dispersed by ultrasound to ensure the casting stability of the resin solution; secondly, it is deaerated and filtered, and cast into a film, while using coagulation bath phase separation and solvent exchange to reduce the drying stress of the graphene-modified reinforced heterocyclic aramid membrane; finally, hot pressing is performed to increase the density of the graphene-modified reinforced heterocyclic aramid membrane.

[0026] In one embodiment of the present invention, Figure 2As shown, the liquid monomer in Q1 is selected from monomers with good solubility and low viscosity, such as MMA, ε-caprolactam, Liquid monomers such as epoxy resins utilize their low viscosity to make graphene easier to disaggregate and evenly disperse. At the same time, the polymer chains form physical entanglements or chemical bonds with the graphene, significantly enhancing interfacial bonding without the need for additional coupling agents. Consequently, the 2-(4-aminophenyl)-5-aminobenzene in the liquid monomer can be in situ polymerized and penetrate into the interlayers of the graphene sheets, thereby yielding 2-(4-aminophenyl)-5-aminobenzimidazole-modified graphene. Graphene modified with substances such as phenylenediaminium, diamines containing heterocyclic structures, and 2-(4-aminophenyl)-5-aminobenzimidazole can also be viewed as graphene-modified substances such as phenylenediaminium, diamines containing heterocyclic structures, and 2-(4-aminophenyl)-5-aminobenzimidazole, which undergo amidation with another component of the aramid synthesis, thereby preparing graphene-modified aramid resin or aramid-modified graphene by bulk polymerization.

[0027] Furthermore, the spinning process in Q3 introduces a high-intensity magnetic field into the pipe and spinneret at both ends of the spinneret, 1 cm to 50 cm away from the nozzle. Since the chain length of the polymer resin is often in a looped state, the dipole moment of the graphene material with a certain functional group content is not zero. Therefore, the high-intensity magnetic field is introduced, and the structural orientation is completed in the pipe and spinneret before spinning, so that the preparation of graphene-modified reinforced aramid fiber can be controlled. At a spinning speed of 1200 m / min, heterocyclic aramid fiber with a mechanical property of 4.8 GPa can be spun. The graphene-modified aramid resin guides the orientation of the aramid molecules during the aramid fiber spinning process, so the spinning speed can be accelerated. The heterocyclic aramid fiber with a mechanical property of 4.8 GPa can be spun at a spinning speed of 1200 m / min, while the traditional heterocyclic aramid fiber spinning can only reach 1000 m / min. This greatly improves its spinning speed, improves equipment utilization and reduces use costs. Taking heterocyclic aramid fiber as an example

[0028] Therefore, the higher the amount of graphene added, the higher the strength of the heterocyclic aramid fiber. However, if the amount added is too high, the viscosity of the aramid resin will increase, and the fluid state of the spinning solution will be affected, resulting in a decline.

[0029] Furthermore, the coagulation bath phase separation and solvent exchange in Q4 are as follows: the membrane is placed in a mixture of water and ethanol for 3-5 minutes to cause non-solvent-induced phase separation, wherein ethanol and n-hexane undergo gradient replacement to reduce drying stress; finally, it is subjected to a hot pressing treatment at 180°C / 5MPa for 10 minutes to increase the density of the membrane; therefore, in the preparation process of the graphene-modified reinforced heterocyclic aramid membrane, the heterocyclic aramid resin can be added to the solvent and stirred at 60°C for 6 hours; then the graphene / pore-forming agent is added and dispersed by ultrasonic wave, wherein the ultrasonic wave operates at 40kHz for 30 minutes, and its viscosity at 25°C is 3000-5000. cP heterocyclic aramid resin solution, thus ensuring the casting stability of heterocyclic aramid resin solution; then the heterocyclic aramid resin solution is filtered through a 100μm filter and filtered under vacuum -0.1MPa for 30min, and then the diaphragm thickness is controlled by a slit coater, with a wet film of 200-300μm and a dry film target of 40-60μm; the coating speed of the slit coater is 0.5-2 m / min; then the diaphragm is placed in a mixture of water and ethanol, wherein the ratio of water to ethanol is 7:3 v / v and the temperature is required to be 25℃, and soaked for 3-5min, so that non-solvent induced phase separation occurs, wherein ethanol and n-hexane are gradiently replaced to reduce drying stress; finally, the diaphragm is treated at 180℃ / 5MPa for 10min to increase the diaphragm density; finally, it is passed through 98% After being treated with H2SO4 vapor for 5 seconds, heterocyclic aramid exhibits high-temperature resistance, flame retardancy, and insulation properties, making it a high-temperature, high-performance transparent film material. Furthermore, aramid separators also possess excellent properties such as high tensile strength, fatigue resistance, UV resistance, and resistance to aging, allowing them to withstand use in extreme environments such as high temperature, high pressure, and high humidity. A coating process is often used to coat PP or PE base films with a 2-3μm aramid coating, which can extend the service life of conventional lithium battery separators and increase their operating temperature. The performance of heterocyclic aramid is significantly higher than that of meta-aramid. A 2-micron thick coating applied to the surface of PP base films is compared as follows:

[0030] In summary, a bulk modified graphene preparation and diaphragm method according to an embodiment of the present invention, when preparing a graphene modified reinforced heterocyclic aramid diaphragm, natural graphite and potassium permanganate can be mixed in a mass ratio of 1:1, and added to concentrated sulfuric acid, and stirred at 0°C for 30 minutes to obtain a graphite oxide precursor; then, aminosilane or borate modifier is added, and the reaction is carried out at 50°C for 2 hours to complete the doping of the bulk; then, the graphite oxide precursor is placed in liquid nitrogen for rapid freezing, and then treated with an ultrasonic cell crusher for 1 hour. , to achieve interlayer peeling; then add ascorbic acid and react at 90℃ for 4 hours to repair lattice defects through reduction reaction, and finally achieve the preparation of complete lamellar structure graphene by controlling the temperature at 2~5℃, and obtain bulk modified graphene; then use the high energy density of laser pulse to ablate the lamellar structure graphene. By using this, graphene microsheets can be accurately cut to create specific shapes, patterns or holes. At the same time, laser pulses are an effective means of reducing graphene oxide, and the photochemical effect of laser can quickly remove oxygen-containing functional groups. , restoring part of the sp2 carbon network structure; therefore, the graphene microsheets can be reshaped and partially reduced by laser pulses to improve their crystallinity; then, by dispersing the flake graphene in a liquid monomer and adding 2-(4-aminophenyl)-5-aminobenzene to the liquid monomer, 2-(4-aminophenyl)-5-aminobenzimidazole-modified graphene can be obtained under the action of in-situ polymerization; wherein the obtained 2-(4-aminophenyl)-5-aminobenzimidazole-modified graphene is added to terephthaloyl chloride / acid; then near-infrared Laser irradiation is performed on a monomer mixture of 2-(4-aminophenyl)-5-aminobenzimidazole-modified graphene and phthaloyl chloride / acid. The graphene absorbs light energy and converts it into heat, inducing localized heating and thermal polymerization, thereby obtaining a graphene-modified reinforced heterocyclic aramid resin. The heterocyclic aramid resin is then added to a solvent and stirred at 60°C for 6 hours. Graphene / pore-forming agent is then added and ultrasonic dispersion is performed at 40 kHz for 30 minutes, resulting in a heterocyclic aramid resin solution with a viscosity of 3000-5000 cP at 25°C, thereby ensuring the casting stability of the heterocyclic aramid resin solution. The heterocyclic aramid resin solution is then filtered through a 100 μm filter and filtered under vacuum at -0.1 MPa for 30 minutes. The separator thickness is then controlled by a slot coater, with a wet film target of 200-300 μm and a dry film target of 40-60 μm. The coating speed of the slot coater is 0.The membrane is then placed in a mixture of water and ethanol (7:3 v / v) at 25°C for 3-5 minutes, allowing non-solvent-induced phase separation to occur. The ethanol is then gradiently replaced with n-hexane to reduce drying stress. Finally, the membrane is treated at 180°C / 5 MPa for 10 minutes to increase its density. Finally, it is treated in a 98% H2SO4 vapor phase for 5 seconds. This results in heterocyclic aramid with high-temperature resistance, flame retardancy, and electrical insulation, making it a high-temperature, high-performance transparent membrane material. Furthermore, aramid membranes exhibit excellent properties such as high tensile strength, fatigue resistance, UV resistance, and resistance to aging, making them suitable for use in extreme environments such as high temperature, high pressure, and high humidity.

[0031] In the description of this specification, the terms "first" and "second" are used for descriptive purposes only and should not be understood to indicate or imply relative importance or implicitly specify the number of the technical features indicated. Therefore, a feature specified as "first" or "second" may explicitly or implicitly include at least one of such features. In the description of the present invention, "plurality" means at least two, for example, two, three, etc., unless otherwise specifically defined.

[0032] In the description of this specification, the reference terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art can combine and combine different embodiments or examples described in this specification and features of different embodiments or examples without contradiction.

[0033] Although the embodiments of the present invention have been shown and described above, it will be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and deform the above embodiments within the scope of the present invention.

Claims

1. A method for preparing bulk-modified graphene, characterized in that: The steps include: S1. Raw material pretreatment: natural graphite and potassium permanganate are mixed in a mass ratio of 1:1, and added to concentrated sulfuric acid to form a graphite oxide precursor. Then, a modifier is added, and the temperature is raised to 50°C for reaction for 2 hours to complete bulk doping; S2. Graphene exfoliation and reduction: The graphite oxide precursor was rapidly frozen in liquid nitrogen and then treated with an ultrasonic cell crusher for 1 hour to achieve interlayer exfoliation. Ascorbic acid was then added and reacted at 90°C for 4 hours to repair lattice defects through a reduction reaction. Finally, the temperature was controlled at 2-5°C to achieve the preparation of complete lamellar graphene and obtain bulk modified graphene. S3. Laser pulses are used to reshape graphene microsheets: The laser's photothermal and photochemical effects are used to reshape the graphene sheets, and the crystallinity of the graphene sheets is reduced and improved.

2. The method for preparing bulk-modified graphene according to claim 1, wherein: In the S1, natural graphite and potassium permanganate are mixed in a mass ratio of 1:1, added into concentrated sulfuric acid, and stirred at 0° C. for 30 minutes to obtain a graphite oxide precursor.

3. The method for preparing bulk-modified graphene according to claim 1, wherein: In step S3, the photothermal effect acts on the surface of the graphene sheet structure through a laser beam, and the laser beam has a high energy density, causing the graphene to undergo a controllable ablation reaction.

4. The method for preparing bulk-modified graphene according to claim 3, wherein: The photochemical effect is achieved by applying a laser beam to the graphene surface, where the induced high-temperature zone triggers controllable oxidation and selective reduction.

5. A method for preparing a bulk-modified graphene membrane, which is applicable to a method for preparing bulk-modified graphene according to any one of claims 1 to 4, and is characterized in that: The following steps are involved: Q1. Preparation of 2-(4-aminophenyl)-5-aminobenzimidazole-modified graphene: Using an in-situ polymerization method, the flake graphene prepared in S3 is dispersed in a liquid monomer, and 2-(4-aminophenyl)-5-aminobenzene is added to the liquid monomer. 2-(4-aminophenyl)-5-aminobenzene is then in situ polymerized in the presence of graphene. The monomer molecules can penetrate between the graphene sheets, and after polymerization, the polymer chains grow directly on the graphene surface or between the sheets. Thus, 2-(4-aminophenyl)-5-aminobenzimidazole-modified graphene can be obtained. Q2. Preparation of graphene-modified reinforced heterocyclic aramid resin: Using a polymerization reaction method, terephthaloyl chloride / acid is added to the 2-(4-aminophenyl)-5-aminobenzimidazole-modified graphene prepared in Q1; a near-infrared laser is then used to irradiate the monomer mixture of 2-(4-aminophenyl)-5-aminobenzimidazole-modified graphene and terephthaloyl chloride / acid; and the graphene absorbs light energy and converts it into heat energy, thereby locally heating and inducing thermal polymerization, thereby obtaining a graphene-modified reinforced heterocyclic aramid resin. Q3. Preparation of graphene-modified reinforced heterocyclic aramid fiber: The graphene-modified reinforced heterocyclic aramid resin in Q2 and an organic solvent such as N,N-dimethylacetamide and calcium chloride are mixed and dissolved. After cooling, a diamine monomer, such as 2-(4-aminophenyl)-5-aminobenzimidazole and p-phenylenediamine, is added. After dissolution, the mixture is cooled again. Then, a diacyl chloride, such as terephthaloyl chloride, is added. The mixture is stirred at a certain temperature at a high speed for polycondensation to obtain a polymer. In this process, the polymerization reaction is carried out in a solution, and the generated polymer is dissolved in the solvent to form a homogeneous system. The heterocyclic aramid fiber is then obtained through a spinning process. Q4. Preparation of graphene-modified reinforced heterocyclic aramid membrane: heterocyclic aramid resin and solvent are prepared into a resin solution; Graphene / pore-forming agent is then added to the resin solution, and the resin solution is dispersed by ultrasound to ensure the casting stability of the resin solution; secondly, it is deaerated and filtered, and cast into a film, while coagulation bath phase separation and solvent exchange are used to reduce the drying stress of the graphene-modified enhanced heterocyclic aramid membrane; finally, hot pressing is performed to increase the density of the graphene-modified enhanced heterocyclic aramid membrane.

6. The method for bulk-modified graphene membrane according to claim 5, characterized in that: The liquid monomer in Q1 is selected from monomers with good solubility and low viscosity, such as MMA, ε-caprolactam, epoxy resin and other liquid monomers.

7. The method for bulk-modified graphene membrane according to claim 5, characterized in that: The spinning process in Q3 introduces a high-intensity magnetic field into the pipe and spinneret at both ends of the spinning plate, 1 cm to 50 cm away from the nozzle, and through a spinning speed of 1200 m / min, it can spin heterocyclic aramid fibers with a mechanical property of 4.8 GPa.

8. The method for bulk-modified graphene membrane according to claim 5, characterized in that: In the above-mentioned Q4, the resin solution needs to be stirred at 60° C. for 6 hours before adding graphene / pore-forming agent to the resin solution; secondly, the degassing filtration will be adopted to filter the solution through a 100 μm filter mesh, and the thickness of the film will be controlled by a slot coating machine.

9. The method for bulk-modified graphene membrane according to claim 5, characterized in that: The coagulation bath phase separation and solvent exchange in Q4 is to place the membrane in a mixture of water and ethanol for 3-5 minutes to cause non-solvent-induced phase separation, wherein ethanol and n-hexane undergo gradient replacement to reduce drying stress; finally, the membrane is subjected to a hot pressing treatment at 180°C / 5MPa for 10 minutes to increase the density of the membrane.

Citation Information

Patent Citations

  • Functionalized graphene and preparation method as well as application thereof

    CN102500422A

  • Preparing method for modified oxidized graphene

    CN105060285A

  • High-flexibility graphene-based supercapacitor based on laser processing and preparation method thereof

    CN113643906A

  • Graphene modified heterocyclic aramid fiber and preparation method thereof

    CN117089944A

  • Aminated graphene oxide / heterocyclic aramid composite fiber and preparation method thereof

    CN119710961A